THE MEANING OF AL-QALB AND DISCLOSURE IN AL-QUR’AN - Agustiar Agustiar (Jurnal Ushuluddin, 2015)
Human being equipped by God Almighty with a variety of gifts which enable them to carry a burden of duties. The gifts are power of the body, vitality and power al-qalb. Islam has made clear necessity of a proper functioning of al-qalb to think in order to develop knowledge. It will help people to carry caliphate duties on earth properly, under the guidance of al-Qur’an and al-Sunnah. One way to enhance thinking of al-qalb required by Islam is dzikir, therefore, someone will find peace of mind and feel close to God. Feeling close to God, a person’s soul will be controlled. Conversely, if a person is not functioning qalb for dzikir, so he will experience drought soul. In al-Qur’an, al-qalb may have some meanings; it refers to the context of verse that contains in it. Moreover, to present the meaning of al-qalb is not always disclosure with the word of al-qalb, but also often disclosure by using the word of al-fuad, al-lub, al-nafs and al-sadr